RHEOLOGICAL PROPERTIES OF WATERMELON JUICE AS AFFECTED BY CONCENTRATION - S., Yosefzadeh Sani,; A., Sharifi; S.A., Mortazavi (Malaysian Journal of Science, 2018)
Rheological properties are presented based on the flow behavior and the deformation of a substance by the action of stress. Among the juices, watermelon is very popular and also very nutritious. In this research, the flow behavior of watermelon juice was determined at concentrations of 40, 50 and 60 0Brix and temperatures of 15, 20 and 30 Â°C.Shear stress data obtained from juices were fitted with rheological models including Newtonian, power law. Also, concentration relation and temperature was determined by Arnius model and exponential law models. Based on the results obtained, both temperature and concentration decreased n values but increased K values. The power law model was also able to predict the dependence on apparent viscosity with concentration with high precision. The combined Arnius-power law model showed a high compliance for the effect of concentration-temperature on the apparent viscosity. It can be concluded that the temperature and concentration completely affect the rheological properties of Iranian watermelon juices Keywords: Concentration, Juice, Rheological properties, Watermelo